Async in C♯ 5.0 - Davies, Alex (Computer software developer) (O'Reilly Media, 2012)
If you're writing one of several applications that call for asynchronous programming, this concise hands-on guide shows you how the async feature in C# 5.0 can make the process much simpler. Along with a clear introduction to asynchronous programming, you get an in-depth look at how the async feature works and why you might want to use it in your application. Written for experienced C# programmers-yet approachable for beginners-this book is packed with code examples that you can extend for your own projects. Write your own asynchronous code, and learn how async saves you from this messy chor.